2008
DOI: 10.1063/1.2908038
|View full text |Cite
|
Sign up to set email alerts
|

Innovative surface acoustic wave sensor for accurate measurement of subatmospheric pressure

Abstract: An original application for surface acoustic wave (SAW) subatmospheric pressure sensor was developed to measure pressure below 100mTorr with very high precision. The basic operating principles and the most significant experimental results of the sensor are presented here. A simple theoretical model is proposed. This sensor provides an efficient measuring solution in a wide range of subatmospheric pressure, which has been inaccessible in past by conventional diaphragm-based SAW sensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…This has been utilized to develop the SAW based strain sensor. Many researchers have addressed significant investigation on SAW strain sensors, these strain based sensors can also detect force, 9 pressure, 10,11 etc. To name a few, Stoney et al reported a passive wireless strain sensor on AT-X quartz with a single port SAW resonator; 12 Konno et al developed an oscillator-based strain sensor using a SAW resonator on lithium niobate (LiNbO 3 ); 13 Hempel et al presented a SAW strain sensor with high precision on Alpha-quartz; 14 and Li et al provided a SAW RFID for temperature and strain sensing on LiNbO 3 .…”
mentioning
confidence: 99%
“…This has been utilized to develop the SAW based strain sensor. Many researchers have addressed significant investigation on SAW strain sensors, these strain based sensors can also detect force, 9 pressure, 10,11 etc. To name a few, Stoney et al reported a passive wireless strain sensor on AT-X quartz with a single port SAW resonator; 12 Konno et al developed an oscillator-based strain sensor using a SAW resonator on lithium niobate (LiNbO 3 ); 13 Hempel et al presented a SAW strain sensor with high precision on Alpha-quartz; 14 and Li et al provided a SAW RFID for temperature and strain sensing on LiNbO 3 .…”
mentioning
confidence: 99%
“…Indeed, at higher pressure, thermal leakage into the surrounding gas (air) increases, which corresponds to a lower resistance to thermal flux between a given surface and the surrounding gas. The resistance value depends on the gas pressure, on the contact surface, on the temperature difference between gas and contact surface and on the surface-air conductivity [3]. The lumped-element model used to simulate the behavior of the sensor is presented in Fig 2. Four main sub-elements have been considered: the supporting PCB (on which the heating resistor and the sensor housing are mounted), the sensor housing, the wire-antenna and the coil.…”
Section: Equivalent System Modelmentioning
confidence: 99%
“…An alternative concept to achieve wireless low pressure measurement with a passive surface acoustic wave (SAW) sensor has been proposed in [3]. It uses the fact that SAW sensors offer the possibility of accurate wireless temperature measurement with fully passive sensors [4].…”
Section: Introductionmentioning
confidence: 99%
“…This variation implies the evolution of the device temperature from Teq to Tf (final equilibrium temperature). The temperature variation ΔT= Teq -Tf can be easily expressed by the following equation [5,6]:…”
Section: Working Principle Of the Sensormentioning
confidence: 99%